Athena Departs for the Acropolis (Od. 7.78–81): A Suggestion. Issue 1 (1st January 2021) - Anghelina, Catalin
Abstract : At the beginning of book 7 of the Odyssey, Athena appears to Odysseus in the form of young girl to instruct him about the Phaeacians. Then, apparently for no reason, she departs for the "house" of Erechtheus on the Athenian Acropolis. I suggest that Athena's destination symbolically reflects the state of affairs between Athena and Odysseus, on the one hand, and Poseidon, on the other. Athena's passing by Marathon in this context symbolizes her entering her sacred land Attica from the north.